1976
DOI: 10.1002/1097-0142(197601)37:1<164::aid-cncr2820370123>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of peripheral lymphocyte counts in patients with breast carcinoma

Abstract: A retrospective study evaluating five-year survival rates in relation to pretreatment lymphocyte counts was undertaken in 453 patients with breast carcinoma. Patients with early tumor stages had higher pretreatment lymphocyte counts than those with advanced tumors: five-year survival in patients with pretreatment counts above 2000 per mm3 was 87% in Stage I, 67% in Stage II, and 57% in Stage III, while the comparable figures in patients with lower counts were 82%, 51%, and 29%. The differences in five-year sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…Although there were no discernable effects of stage 1 cancer on immune function, there was a gradual decline subsequently in stages 2 through 4, with a decrease in T-lymphocyte function in stage 2, in T-and B-lymphocyte function in stage 3, and an additional decrease in NK cell function in stage 4. Levels of lymphocyte and WBCs in patients with malignant tumors are predictive of outcomes, with high risk for recurrence and very low survival rate when levels fall below the normal range [50][51][52]. Chemotherapy and radiotherapy can further decrease immune function through their targeted effect on T-and B-lymphocyte cells, which play an important role in acquired immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no discernable effects of stage 1 cancer on immune function, there was a gradual decline subsequently in stages 2 through 4, with a decrease in T-lymphocyte function in stage 2, in T-and B-lymphocyte function in stage 3, and an additional decrease in NK cell function in stage 4. Levels of lymphocyte and WBCs in patients with malignant tumors are predictive of outcomes, with high risk for recurrence and very low survival rate when levels fall below the normal range [50][51][52]. Chemotherapy and radiotherapy can further decrease immune function through their targeted effect on T-and B-lymphocyte cells, which play an important role in acquired immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Immune infiltration influences prognosis and response to therapies . Notably high CD8+ T cell counts associate with better overall survival in estrogen receptor (ER) negative breast cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral blood lymphocyte count has also been reported to have a positive association with 5 year survival and disease-free survival rates (Papatestas et al, 1976). Immune competence, measured by a summary score derived from in vitro lymphocyte function tests and in vivo cutaneous reactivity, has been related to prognosis though in this study the peripheral lymphocyte count was not found to have prognostic value (Adler et al, 1980).…”
mentioning
confidence: 99%